Produção do comum e políticas de saúde mental infantojuvenis: convergências e distanciamentos - Rocha, Laura Sanches (2025)
Public policies for child and adolescent mental health in Brazil have a recent history of institutionalization, dating back approximately the last twenty-five years. Since then, mental health care for children and adolescents has been shaped by the understanding of these individuals as subjects of rights and by the guarantee of their care in freedom, following the principles of the Psychiatric Reform and Human Rights. In parallel, the interdisciplinary concept of the “production of the common” has gained prominence as a political principle aimed at opposing the neoliberal and capitalist way of life. This concept, inspired by the Philosophy of Difference, has been explored in the field of Collective Health, emphasizing collective, community-based, and participatory practices, and it may enter into dialogue with the assumptions of the Brazilian Psychiatric Reform. This research seeks to build a bridge between child and adolescent mental health policies and the concept of the production of the common, identifying, through the discourse present in key policy documents, possible correlations—whether potentially conducive to or suppressive of the production of the common. The general objective of this project is to analyze how the production of the common correlates with federal mental health policies for children and adolescents. To this end, the following specific objectives are proposed: (a) to map and analyze official documents that support child and adolescent mental health policies in Brazil; and (b) to identify correlations between the statements guiding public mental health policies for children and adolescents and the production of the common. To achieve these objectives, a document analysis methodology is employed, structured in the following stages: identification of the main documents to be analyzed, floating reading, selective reading, categorization of selected excerpts, and descriptive and reflective data analysis. Preliminary results indicate possible dialogues between the discourses of child and adolescent mental health policies and the production of the common, which were systematized into two axes: (1) Discourses potentially conducive to the common (including topics such as Guarantee of rights, Social inclusion, Social control, Territory, Work and network articulation, Collective care proposals, Intersectoriality, Universal access to services, Collaborative work, Health as a process of production, Subject autonomy, Comprehensiveness, Support for teamwork, and Horizontality); and (2) Discourses potentially suppressive of the common, which include practices and narratives that may inhibit common-producing practices (such as the Risk of pathologizing childhood and adolescence, and Fragmented work processes). It is expected that the results of this research will contribute to the improvement of intersectoral policies aimed at children and adolescents, to the fields of Mental Health and Collective Health, as well as to the field of Occupational Therapy.